DATA-BASED ACADEMIC SUPERVISION IN IMPROVING ELEMENTARY SCHOOL TEACHERS’ PEDAGOGICAL COMPETENCE - Cucu Juhariah; Eva Dianawati Wasliman; Sri Handayani (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
Academic supervision is one of the principal's primary duties and responsibilities in ensuring the optimal quality of the learning process. Further research is essential to understand the principal's implementation of academic supervision and to determine its impact on teachers' pedagogical competence. This research was conducted in Ibun District. Data were collected through observation, interviews, and documentation. This study employed a qualitative approach, utilizing a case study method. The research results indicate that academic supervision plays a significant role in enhancing teachers' pedagogical competence. Overall, supervision serves not only as oversight but also as a collaborative process that encourages teacher reflection and innovation. Analysis based on the stages of supervision (planning, organizing, implementing, and monitoring) shows that each stage is interrelated and contributes to improving pedagogical competence.